Wkład biskupa Stanisława Karnkowskiego w dzieło recepcji reformy trydenckiej w diecezji włocławskiej - Gręźlikowski, Janusz (Prawo Kanoniczne, 2001)
The resolutions and edicts of the Council of Trent (1545-1563) made some requirements to acquire and implement into force the regional Churches. A reception of reforms of Trent was now carried out by legislative and pastoral activity of bishops - administrators of the dioceses. In the Diocese of Włocławek (these days called Kujawsko-Pomorska Diocese) the reception of Tridentinum at this very beginning time hoppened on ardour, wise and hearty advocate of Church’s revival, it’s structures and hierarchy - bishop Stanislaw Karnkowski. He realised so well, that revival priesthood and reforming the religion’s life must come from the point of clergy’s reforming, keeping the ecclesiastical and revival of sacramental life with instructing the truth of faith. He striven for this by legislative during diocese’s synods held in 1568 and 1579. He supported legislative and pro-reforming activy by issuing his legislative set and also „Reprimands” and „Admonitiones” - liturgical agenda, useful for iniform the liturgy, so helpful for priests. In 1569 he fouded theological seminary in Włocławek. Deep analysis of his legislative activity must lead into conclusion, that he laid the fundations of the new structures for religion’s, priesthood’s and church’s life established by the Council of Trent. Bishop Karnkowski - being the bishop of Włocławek and then the Metropoliotan of Gniezno - was characterised by great legislative activity. The acceptance of Trent’s resolutions in Kujowsko-Pomorska Diecese and also during province’s synod in Piotrkow held in 1589 presided by bishop Karnkowski, was a base for further reforming of religion’s life in the Polish Nation and conducted to the intensification and development of the synod’s activity in the dioeceses, also in the Diocese of Włocławek.